Decreased corticosensitivity in quiescent Crohn's disease : An ex vivo study using whole blood cell cultures - FRANCHIMONT, D; LOUIS, E; DUPONT, P; VRINDTS-GEVAERT, Y; DEWE, W; CHROUSOS, G; GEENEN, V; BELAICHE, J (Digestive diseases and sciences, 1999)
Corticosensitivity influences the degree and the duration of an inflammatory reaction by altering target cell responses to endogenous and/or exogenous glucocorticoids. Indeed, different clinical responses to glucocorticoids have been observed among patients with Crohn's disease, suggesting different degrees of corticosensitivity in these subjects. The purpose of this study was to compare the corticosensitivity of patients with quiescent Crohn's disease to that of healthy subjects (HS). Nineteen patients with quiescent Crohn's disease and 14 HS were studied; all patients were steroid-free for at least six months; 7 of the 19 were corticosteroid-dependent (CSD) and treated with nonglucocorticoid immunosuppressants at the time of the study. Corticosensitivity was measured by the inhibition of LPS-induced cytokine secretion in whole blood cell cultures treated with increasing concentrations (10(-9) to 10(-6) M) of dexamethasone. Tumor-necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6), and interleukin-1 beta (IL-1 beta) were measured using specific immunoassays. Crohn's disease patients had a markedly decreased dexamethasone-mediated inhibition of TNF-alpha (P < 0.01), IL-6 (P < 0.001), and IL-1 beta (P < 0.01) compared to healthy subjects, with a shift of the dexamethasone dose-response curve to the right. No significant differences in the basal and LPS-stimulated secretion of the three cytokines were observed between CSD and non-CSD patients, and both subgroups of patients had similar degrees of dexamethasone-mediated cytokine inhibition. We conclude that patients with Crohn's disease have a significant decrease in the corticosensitivity of their leukocytes. This may be related to a specific genetic/constitutional background and/or could be acquired, due to inflammation-related endocrine and/or immune factors.